A note on a bound of Adan-Bante - Xiaoyou Chen (Український математичний журнал, 2014)
Let G be a finite solvable group and let χ be a nonlinear irreducible (complex) character of G. Also let η (χ) be the number of nonprincipal irreducible constituents of χχ, where χ denotes the complex conjugate of χ. Adan-Bante proved that there exist constants C and D such that dl (G/ ker χ) ≤ C η (χ) +D. In the present work, we establish a bound lower than the Adan-Bante bound for η (χ) > 2